(untitled) (Proceedings of Southern Federal University. Philology, 2021)
Ekaterina V. Surovtseva (Moscow, Russian Federation) One of the urgent issues of modern Russian studies is the study of letters to the power of Russian writers. It is legitimate to single out these addresses in a special genre, which, in contrast to the genre of friendly writing, has practically not been studied. Fedor Dostoevsky wrote letters to Alexander I, V. A. Dolgorukov, A. E. Timashev, A. A. Suvorov, heir to the throne A. A. Romanov, and Grand Duke K. K. Romanov. Of particular note is the voluminous correspondence between Dostoevsky and K.P. Pobedonostsev – correspondence between a writer and an official of such a high rank is very rare (it should be noted that the addresser and the addressee were connected not only by business, but also by personal relations). The subjects of Dostoevsky’s letters to the authorities are very diverse – requests to move to the capital, creativity, literary and social life in Russia and Europe, the publication of “Citizen” and others. On the basis of F.M. Dostoevsky’s letters to the Emperor, the Tsareviches and their confidants of various ranks, one can trace the relationship with the authorities and clarify a number of already obtained facts and assessments. The messages of Russian writers to power are a special kind of epistolary genre that has both aesthetic value and is a historical document – evidence of the relationship between power and literature in our country. Obviously, the authorities were interested in cooperation with writers, and specific rulers showed interest in the work and in the personality of Dostoevsky. Key words: “letter to the sovereign”, “letter to the tsar”, epistolary genre, F. M. Dostoevsky, Russian literature of the 19th century. DOI 10.18522/1995-0640-2021-2-147-155